Observations of Vocabulary Activities during Second- and Third-Grade Reading Lessons - Nicole Sparapani; Joanne F. Carlisle; Carol McDonald Connor (MDPI AG, 2018)
Vocabulary instruction is a critical component of language and literacy lessons, yet few studies have examined the nature and extent of vocabulary activities in early elementary classrooms. We explored vocabulary activities during reading lessons using video observations in a sample of 2nd- and 3rd-grade students (n = 228) and their teachers (n = 38). Teachers spent more time in vocabulary activities than has been previously observed. In the fall, 28% of their literacy block was devoted to vocabulary in 2nd grade and 38% in 3rd grade. Our findings suggest that vocabulary activities were most likely to take place prior to reading a text—teachers rarely followed-up initial vocabulary activities after text reading. Analysis of teachers’ discourse moves showed more instructional comments and short-answer questions than other moves; students most frequently engaged in participating talk, such as providing short, simple answers to questions. Students engaged in significantly more talk during vocabulary activities (including generative talk such as initiating an idea) in the spring of 3rd grade than the spring of 2rd grade. These data contribute descriptive information about how teachers engage their students in vocabulary learning during the early elementary years. We discuss implications for practice and future research directions.